(untitled) (Research, Society and Development, 2021)
This article sought to carry out a bibliographical survey, of a narrative nature, on dental care for pregnant women. Virtual searches were performed in the databases: PubMed, Cochrane Library, LILACS and the Scielo virtual library. For this, the central question was established: "How is dental care for pregnant women?" Complete studies were included to assess the dental care provided to pregnant women. Therefore, the articles were critically analyzed in this review. This study aims to analyze the literature on dental care for pregnant women, due to the special need caused by changes in their bodies. It is found that many dental surgeons refuse dental care to pregnant women for fear of causing abortion due to physiological changes that occur during the gestational period, especially in the critical period of pregnancy (first trimester). So, they choose to perform the appropriate procedures at another period of pregnancy, because they feel safer to carry out the practice. [services, inevitably exposing its brands in social networks. The work evaluates the interaction of the organizations with the users in order to fulfill the mission of defending their brand in the face of judgments that may negatively expose the products and services of the brand that over the years struggles to survive the current economic situations of the country. Therefore, the present work aims to provide clarifications and recommendations on clinical behavior through scientific evidence related to dental care for pregnant women, enabling the establishment of an adequate treatment plan, a safe, humane and effective care.